Evaluation of the Performance and Optimization Advices on 4-Sector Deployment in LTE Networks - Chen Ma (Dianxin kexue)
As one feasible way to improve cell site occupation ratio and network coverage with the increasingly scarcity of communication cell site resources，4-sector deployment in LTE networks was introduced. The concept of 4-sector deployment and the related interference problem were studied. Both theoretical and field test evaluation performances were shown to indicate the impact of the deployment to networks. To solve the interference problem of 4-sector deployment，two solutions，single-frequency network（SFN）and radio frequency（RF）optimization techniques were proposed and analyzed. The performance gain of these two solutions were compared in existing network scenarios. With all the studies and evaluation，the final advices on 4-sector deployment and optimization were proposed.